2012
DOI: 10.1021/jp302027y
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Functionalization of Multiwalled Carbon Nanotube by a Polythiophene-Based Compatibilizer: Reinforcement and Conductivity Improvement in Poly(vinylidene fluoride) Films

Abstract: A new compatibilizer (P2) containing thiophene moiety and poly(dimethylamino ethyl methacrylate) (PDMAEMA) group is prepared by atom transfer radical polymerization (ATRP). The dispersion of multiwalled carbon nanotube (MWNT) with P2 in N,N-dimethylformamide (DMF) is stable for >3 months. The UV–vis spectrum of the MWNT/P2 dispersion shows a blue shift, and the photoluminescence (PL) spectrum also indicates a quenching suggesting a significant interaction between MWNT and P2. SEM and TEM micrographs suggest a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 84 publications
(103 reference statements)
4
59
1
2
Order By: Relevance
“…Carboxylation is the widely used approach in order to produce stable water dispersion of carbon nanotubes and for further CNTs functionalization via carboxylic groups. In addition, CNTs can be further stabilized by chemically attached organic reagents or polymer chains [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylation is the widely used approach in order to produce stable water dispersion of carbon nanotubes and for further CNTs functionalization via carboxylic groups. In addition, CNTs can be further stabilized by chemically attached organic reagents or polymer chains [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to induce crystalline polar β phase formation in PVDF by doping chemical agents. Boey [15] and Mandal [16] prepared PVDF composites by adding carbon nanotubes into PVDF, which showed that the composite has a higher crystalline β phase content. However, carbon nanotubes are hard to disperse and cost a lot.…”
Section: Introductionmentioning
confidence: 99%
“…After copolymerization, weight loss in the range of 100-700 °C increases to 28.6% and 27.4% in HNTs-g-PHD50 and HNTs-g-PHD70 respectively. The copolymer chains exhibit two stages of weight loss; the first one at 260 °C related to thermal decomposition of oxygen containing side chain groups and the second one at 420 °C originated from decomposition of polymer backbones [52]. Also, the second stage of degradation of HNTs at 497.6 °C decreases to 477.0 °C by polymer attachment (Figure 3 The surface morphology of HNTs before and after polymer grafting was studied by SEM as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%